Synchronous Remote Rendering for VR. (20th July 2021) - Kelkkanen, Viktor; Fiedler, Markus; Lindero, David
Abstract : Remote rendering for VR is a technology that enables high-quality VR on low-powered devices. This is realized by offloading heavy computation and rendering to high-powered servers that stream VR as video to the clients. This article focuses on one specific issue in remote rendering when imperfect frame timing between client and server may cause recurring frame drops. We propose a system design that executes synchronously and eliminates the aforementioned problem. The design is presented, and an implementation is tested using various networks and hardware. The design cannot drop frames due to synchronization issues but may on the other hand stall if temporal disturbances occur, e.g., due to network delay spikes or loss. However, experiments confirm that such events can remain rare given an appropriate environment. For example, remote rendering on an intranet at 90 fps with a server located approximately 50 km away yielded just 0.002% stalled frames while rendering with extra latency corresponding to the duration of exactly one frame (11.1 ms at 90 fps). In a LAN without extra latency setting, i.e., with latency equal to locally rendered VR, 0.009% stalls were observed while using a wired Ethernet connection and 0.058% stalls when using 5 GHz wireless IEEE 802.11 ac.